Climate change impacts on Arctic ecosystems and associated feedbacks - Fauchald, Per; Christensen, Torben Røjle; Christensen, Tom (Frontiers in Environmental Science, 2026)
Climate change is currently reshaping Arctic ecosystems, with highly uncertain future outcomes. In the best-case scenario, warming could lead to the replacement of Arctic ecosystems by more diverse and productive sub-Arctic or temperate ecosystems, which may serve as net carbon sinks. However, recent research indicates that environmental disturbances caused by rapid warming could transform these ecosystems into heavily perturbed and degraded states, resulting in a net release of carbon to the atmosphere. The eventual outcome depends on the scale and pace of environmental changes, as well as the extent of other human disturbances in the region. To navigate these changes, we argue that it is crucial for Arctic nations to collaborate in monitoring and ecosystem-based management while developing policy-relevant pathways and scenarios to guide adaptation in a rapidly changing Arctic.